2016
DOI: 10.3389/fmicb.2016.01910
|View full text |Cite
|
Sign up to set email alerts
|

Purification of Antilisterial Peptide (Subtilosin A) from Novel Bacillus tequilensis FR9 and Demonstrate Their Pathogen Invasion Protection Ability Using Human Carcinoma Cell Line

Abstract: This study focuses on isolation, screening, and characterization of novel probiotics from gastrointestinal tract of free-range chicken (Gallus gallus domesticus). Fifty seven colonies were isolated and three isolates (FR4, FR9, and FR12) were selected and identified as Lactobacillus gasseri FR4, Bacillus tequilensis FR9, and L. animalis FR12 by 16S rRNA sequencing. Three strains were able to survive in stimulated acidic and bile conditions and inhibit the growth of pathogens. Especially, FR9 exhibited maximum … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 55 publications
8
16
0
Order By: Relevance
“…In present study, all Bacillus strains showed no hemolysis. Parveen et al, (2016) had worked on probiotic potential of Bacillus strains and their results were in accordance with present findings in which B. tequilensis FR9 showed no hemolysis. Similar results were given in the one of the experiment of Luis-Villasenor et al (2011), who noted that Bacillus species showed alpha hemolysis.…”
Section: Resultssupporting
confidence: 90%
See 4 more Smart Citations
“…In present study, all Bacillus strains showed no hemolysis. Parveen et al, (2016) had worked on probiotic potential of Bacillus strains and their results were in accordance with present findings in which B. tequilensis FR9 showed no hemolysis. Similar results were given in the one of the experiment of Luis-Villasenor et al (2011), who noted that Bacillus species showed alpha hemolysis.…”
Section: Resultssupporting
confidence: 90%
“…The strains B. tequilensis was the most significantly (p<0.05) resistant strain (Table 4). Similar results were given by Parveen et al (2016). A vital property of the probiotic strains is the antipathogenic activity.…”
Section: Resultssupporting
confidence: 83%
See 3 more Smart Citations